2022
DOI: 10.1109/jlt.2022.3160101
|View full text |Cite
|
Sign up to set email alerts
|

DSP-Based Link Tomography for Amplifier Gain Estimation and Anomaly Detection in C+L-Band Systems

Abstract: A successful migration from current C-band based optical networks to a multiband scenario primarily depends on the development of solutions that can reliably measure physical properties of optical links over broad spectral transmission windows. Additionally, these solutions must be capable of delivering wavelength-dependent and spatially-resolved indicators that can empower network operators to identify faults before they lead to severe service disruptions. Recently, the exploitation of receiver based digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Second, this single-channel analysis is immune to the interference originated from adjacent carriers, i.e., cross-channel interference. Therefore, we believe that a C+L-band multi-channel analysis is an interesting and more realistic study that would finally complement the discussions present in [16] and [17].…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Second, this single-channel analysis is immune to the interference originated from adjacent carriers, i.e., cross-channel interference. Therefore, we believe that a C+L-band multi-channel analysis is an interesting and more realistic study that would finally complement the discussions present in [16] and [17].…”
Section: Introductionmentioning
confidence: 65%
“…In [16], it was also shown that the link tomography can directly support the identification of failures such as anomalous gain tilt imposed by malfunctioning amplifiers. Recently, our work published in [17] also successfully demonstrated that another type of amplification fault, i.e., the narrowband gain compression caused by the spectral hole-burning (SHB) effect, can be likewise captured by using the link tomography.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations